Under Construction: Agape as Comparative Category and Christian Criterion of Hindu Truth - Locklin, Reid B. (Toronto journal of theology, 2014)
In an influential 1985 article, Peggy Starkey proposed radical love of neighbour, agape, as the "central, saving revelation" of God in Christ and thus the primary "criterion" for Christians to recognize saving truths in other religious paths. In this essay, I survey several recent works in Hindu-Christian comparative theology, with an eye to Starkey's proposal and the consequences of translating distinctively Hindu texts and traditions into the idiom of Christian love. Whether one focuses on the more devotional or the non-dualist traditions, the literature reveals an animated conversation on the question of love—including agapic love—and thus supports the continuing relevance of Starkey's claim. At the same time, proper to the distinctive aims and methods of comparative theology, such love has functioned less as a criterion for evaluation than as a conduit for new or renewed insights into Christian discipleship. Christian comparativists are increasingly pursuing the question of love with their Hindu interlocutors, not primarily to test the truth of these traditions but to learn how to love more fully and more faithfully, as Christians and as inter-religious theologians.